2017
DOI: 10.1002/acr.23092
|View full text |Cite
|
Sign up to set email alerts
|

Early Disease Activity or Clinical Response as Predictors of Long‐Term Outcomes With Certolizumab Pegol in Axial Spondyloarthritis or Psoriatic Arthritis

Abstract: ObjectiveEarly identification of patients unlikely to achieve good long‐term disease control with anti–tumor necrosis factor therapy in axial spondyloarthritis (SpA) and psoriatic arthritis (PsA) is important for physicians following treat‐to‐target recommendations. Here we assess associations between disease activity or clinical response during the first 12 weeks of treatment and attainment of treatment targets at week 48 in axial SpA and PsA patients receiving certolizumab pegol.MethodsThe relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…Concerning PsA, we and others have found a favorable effect of MTX co-administration 15,20 , while a report from the COnsortium of Rheumatology Researchers Of North America US-based registry found no effect 21 . A systematic literature review showed that the use of MTX prolongs TNFi 23,24 . Interestingly, major response rates within the first year in our present cohort were high and comparable to those in previous studies 5,15,25,26 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Concerning PsA, we and others have found a favorable effect of MTX co-administration 15,20 , while a report from the COnsortium of Rheumatology Researchers Of North America US-based registry found no effect 21 . A systematic literature review showed that the use of MTX prolongs TNFi 23,24 . Interestingly, major response rates within the first year in our present cohort were high and comparable to those in previous studies 5,15,25,26 .…”
Section: Rheumatologymentioning
confidence: 99%
“…[4] Early response to certolizumab pegol in patients with psoriatic arthritis has also been associated with greater achievement of treatment targets at later time points; however, skin response in the total population was not investigated. [5] A c c e p t e d…”
Section: Introductionmentioning
confidence: 99%
“…Early clinical improvements were shown to predict 1 or 5 years clinical responses in SpA patients, albeit in the context of clinical trials of TNFi [410,411]. Interestingly, major response rates within the first year in the present cohort were high and comparable to those in previous studies [191,227,346,412].…”
Section: Discussionsupporting
confidence: 82%